2014
DOI: 10.1016/j.tox.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to p,p′-dichlorodiphenyldichloroethylene (DDE) induces fasting hyperglycemia without insulin resistance in male C57BL/6H mice

Abstract: Approximately 8.3% of the United States (U.S.) population have either diagnosed or undiagnosed diabetes mellitus. Out of all the cases of diabetes mellitus, approximately 90–95% of these cases are type 2 diabetes mellitus (T2D). Although the exact cause of T2D remains elusive, predisposing factors include age, weight, poor diet, and a sedentary lifestyle. Until recently the association between exposure to environmental contaminants and the occurrence of diabetes had been unexplored. However, recent epidemiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 38 publications
(59 reference statements)
4
32
0
Order By: Relevance
“…Exposures to organochlorine insecticides (DDE, HCB, and ɣ-HCH) have led to increased body weight gain in rodents (Table 4) (Chadwick et al, 1988; Howell et al, 2014; Howell et al, 2015; Villeneuve et al, 1977), including a study of parental trans-generational exposure to DDT linked to increased obesity rate in the offspring (Skinner et al, 2013). Similarly, others reported that perinatal exposure to DDT was linked to significant weight gain, but only in female offspring (La Merrill et al, 2014) or reduced weight was reported after dieldrin exposure (Shakoori et al, 1984).…”
Section: Effects Of Insecticide Exposure On Glucose and Lipid Metamentioning
confidence: 99%
“…Exposures to organochlorine insecticides (DDE, HCB, and ɣ-HCH) have led to increased body weight gain in rodents (Table 4) (Chadwick et al, 1988; Howell et al, 2014; Howell et al, 2015; Villeneuve et al, 1977), including a study of parental trans-generational exposure to DDT linked to increased obesity rate in the offspring (Skinner et al, 2013). Similarly, others reported that perinatal exposure to DDT was linked to significant weight gain, but only in female offspring (La Merrill et al, 2014) or reduced weight was reported after dieldrin exposure (Shakoori et al, 1984).…”
Section: Effects Of Insecticide Exposure On Glucose and Lipid Metamentioning
confidence: 99%
“…Adipose tissue synthesises triacylglycerol (TAG) from glucose 67,68 , such that glucose uptake rates can be used to investigate metabolic function of adipose tissue. Glucose uptake is altered by POPs at tissue and the whole animal level in other animals [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] . Of glucose taken up by adipose, 20% is stored as TAG, and 70% is used to synthesise lactate 67 .…”
Section: Introductionmentioning
confidence: 99%
“…Blood was obtained through cardiac puncture, allowed to clot, and the serum separated by centrifugation. Serum was used to measure fasting insulin levels (Mercodia mouse insulin ELISA), triglyceride (Cayman Chemical), and total cholesterol (Cayman Chemical) levels as previously described (Howell et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Digital images were captured at 100× magnification for visual confirmation of macrovesicular steatosis. To quantify the degree of hepatic steatosis, liver triglyceride levels were measured as previously performed and expressed at micromoles of triglyceride (TG) per milligram of protein (Howell et al, ; Howell and Mulligan, ).…”
Section: Methodsmentioning
confidence: 99%